Kinerja Lembaga Swadaya Masyarakat Di Kota Makassar dalam Mewujudkan Good Governance Tahun 2010-2012 - Mulda, Rahmayandi; Suranto, Suranto (Journal of Governance and Public Policy, 2014)
The problems in this study include how the performance of the NGOsis in achieving Good Governance and the factorsthat affect the NGOs in achieving Good Governance. The study aimed to know and describe the performance of theNGOs to achieve Good Governance and also to know the factors that influence the performance of the NGOs in doingso. The study showed that the performance of the NGOs in Makassar to achieve good government from 2010 to 2012is good. This good performance works on the objects under the study which are Kopel, ACC, LBH APIK, and OXFAM andcan be seen from the works that those NGOs conducted such as encouraging financial transparencyof the localgovernment, enhancing the accountability of the work of local government, encouraging the rule of law in the country,developing agreement orientation to the government, encouragingthe equality between the government and thepublic, responding to a variety of problems that occur in the country, and encouraging the efficiency and effectivenessof government work. Meanwhile, the factors that affect the performance of the NGOs in achieving Good Governanceare the human resource factors, the donating agencies, the accountability of the NGOs, the independence, the networks,the idealism and leadership. The government should facilitate the NGOs which have good work performanceand are well-trusted by the public as they have contributions to the nation development. The NGOs should receive aserious attention by all related parties from the government and the society. It is because the NGOs function as abridge between the public and the government. As the NGOs are directly connected with the donors from the developedcountries, it is possible that there can be particular intentions or interests that those countries put through theNGOs.